A new species of spiny Rineloricaria (Siluriformes: Loricariidae) from the Rio Paraíba do Sul basin and costal rivers from Rio de Janeiro State - da Costa Silva, Guilherme José; de Souza Da Costa E Silva, Gabriel [UNESP]; Oliveira, Claudio [UNESP] (Magnolia Press, 2022)
Although the genus Rineloricaria is widely distributed in the Neotropical region, its species usually occupy single drainages with high habitat fidelity. Rineloricaria species show evident sexual dimorphism with hypertrophied odontodes in sexually mature males. Here, we describe a new species of Rineloricaria present in the Rio Paraiba do Sul basin and coastal rivers in Rio de Janeiro State. The new species has extreme sexual dimorphism making possible to differentiate it from all congeners. The new species can also be separated from other sympatric species by morphometric characteristics and dermal plates pattern.
Keywords: Biodiversity; Catfish; Loricariinae; Odontoid; Paraiba do Sul